A philosophical approach to the value of biographical narratives in ancient philosophy in response to historiographical skepticism - RUIZ SÁNCHEZ , José (Utopía y Praxis Latinoamericana, 2025)
The approach to the biographical genre, when referring to the life, work, and opinions of ancient philosophers, constitutes a genre with a distinctive typology to the extent that its narrative about the philosophers' lives serves as an introduction to the hermeneutics of their philosophies. In this article, we will attempt to argue about the relevance of these biographies understood as an instrument that complements, while shaping, the philosophy of ancient thinkers, in contrast to a historicist view of biography as a genre that requires the verification of facts.